Alcohol consumption, cardiac biomarkers, and risk of atrial fibrillation and adverse outcomes - Csengeri, Dora; Sprünker, Ngoc-Anh; Di Castelnuovo, Augusto; Niiranen, Teemu; Vishram-Nielsen, Julie Kk; Costanzo, Simona; Söderberg, Stefan; Jensen, Steen M; Vartiainen, Erkki; Donati, Maria Benedetta; Magnussen, Christina; Camen, Stephan; et al. (European heart journal, 2021)
Abstract Aims There is inconsistent evidence on the relation of alcohol intake with incident atrial fibrillation (AF), in particular at lower doses. We assessed the association between alcohol consumption, biomarkers, and incident AF across the spectrum of alcohol intake in European cohorts. Methods and results In a community-based pooled cohort, we followed 107 845 individuals for the association between alcohol consumption, including types of alcohol and drinking patterns, and incident AF. We collected information on classical cardiovascular risk factors and incident heart failure (HF) and measured the biomarkers N-terminal pro-B-type natriuretic peptide and high-sensitivity troponin I. The median age of individuals was 47.8 years, 48.3% were men. The median alcohol consumption was 3 g/day. N = 5854 individuals developed AF (median follow-up time: 13.9 years). In a sex- and cohort-stratified Cox regression analysis alcohol consumption was non-linearly and positively associated with incident AF. The hazard ratio for one drink (12 g) per day was 1.16, 95% CI 1.11–1.22, P < 0.001. Associations were similar across types of alcohol. In contrast, alcohol consumption at lower doses was associated with reduced risk of incident HF. The association between alcohol consumption and incident AF was neither fully explained by cardiac biomarker concentrations nor by the occurrence of HF. Conclusions In contrast to other cardiovascular diseases such as HF, even modest habitual alcohol intake of 1.2 drinks/day was associated with an increased risk of AF, which needs to be considered in AF prevention. Graphical Abstract Hazard ratio for incident atrial fibrillation for alcohol consumption in gram per day by non-linear Cox regression plotted on the log-scale (N = 92 452). The model uses age as time scale and is sex and cohort stratified. The reference value is 0 g/day.